Burnout and depressive symptoms in intensive care nurses: relationship analysis - Eduardo Motta de Vasconcelos; Milva Maria Figueiredo De Martino; Salomão Patrício de Souza França
ABSTRACT Objective: To analyze the existence of a relationship between burnout and depressive symptoms among intensive care unit nursing staff. Method: A quantitative, descriptive, cross-sectional study with 91 intensive care nurses. Data collection used a sociodemographic questionnaire, the Maslach Burnout Inventory - Human Services Survey, and the Beck Depression Inventory - I. The Pearson test verified the correlation between the burnout dimension score and the total score from the Beck Depression Inventory. Fisher's exact test was used to analyze whether there is an association between the diseases. Results: Burnout was presented by 14.29% of the nurses and 10.98% had symptoms of depression. The higher the level of emotional exhaustion and depersonalization, and the lower professional accomplishment, the greater the depressive symptoms. The association was significant between burnout and depressive symptoms. Conclusion: Nurses with burnout have a greater possibility of triggering depressive symptoms.